2018
DOI: 10.1186/s12879-018-3609-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient and health care services delays for tuberculosis diagnosis in Italy: a cross-sectional observational study

Abstract: BackgroundPrompt diagnosis of active tuberculosis (TB) has paramount importance to reduce TB morbidity and mortality and to prevent the spread of Mycobacterium tuberculosis. Few studies so far have assessed the diagnostic delay of TB and its risk factors in low-incidence countries.MethodsWe present a cross-sectional multicentre observational study enrolling all consecutive patients diagnosed with TB in seven referral centres in Italy. Information on demographic and clinical characteristics, health-seeking traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
(34 reference statements)
5
36
3
5
Order By: Relevance
“…The most frequent reason for the patient delay is that patients with TB tend to neglect the symptoms [22]. In a previous study performed in Italy, one of the most frequent reasons for delays in treatment was the light nature of the symptoms (82%) and feeling healthy (76%) [23]. In our study, we found that patients whose first symptoms were cough, weight loss, night sweats, exhaustion, and hoarseness tended to neglect these symptoms and consult a physician much later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent reason for the patient delay is that patients with TB tend to neglect the symptoms [22]. In a previous study performed in Italy, one of the most frequent reasons for delays in treatment was the light nature of the symptoms (82%) and feeling healthy (76%) [23]. In our study, we found that patients whose first symptoms were cough, weight loss, night sweats, exhaustion, and hoarseness tended to neglect these symptoms and consult a physician much later.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that the diagnosis delay was significantly shorter in patients who were consulted by chest physicians, dispensary physicians, and ER ward physicians than by other physicians. In a study performed in Italy, it was observed that the delay was longer when patients were first evaluated by family physicians [23]. According to a study performed in Ethiopia, seeing a family physician first was one of the independent indicators of the health system [29].…”
Section: Discussionmentioning
confidence: 99%
“…Não se pode afirmar como tal questão influencia na adesão de homens e mulheres ao tratamento da tuberculose, entretanto, reafirma-se realidade condicionada socialmente ao gênero (Kergoat, 1996;Toledo, 2008;Biroli, 2014;Herrero et al, 2015). (Bertolozzi, 2005;Andrade et al, 2017;PERI et al, 2018).…”
Section: I S C U S S ã O | 141unclassified
“…A identificação da sintomatologia, aliada à busca pelo serviço adequado para o diagnóstico da TB pelos pacientes pode auxiliar no diagnóstico precoce e contribuir para dirimir o sofrimento dos pacientes, com consequências importantes na adesão ao tratamento (Wang et al, 2008;Dantas et al, 2018;Yang et al, 2018). De fato, o atraso no diagnóstico é uma das causas da disseminação do bacilo de Koch e consequentemente do aumento da incidência (Jurcev-Savicevic et al, 2013;Cai et al, 2015;Cohen et al, 2018;Dantas et al, 2018;Peri et al, 2018).…”
Section: Categoria I -Gênero E Tuberculoseunclassified
See 1 more Smart Citation